From Perception to Purchase: How Price, Brand Image, and Technology Shape Consumer Choices - Soetjipto, Audrey Hans; Lie, Michelle Gabriel; Halim, Valencia Thania; Wen, Valeria Griselda; Juliana, Juliana (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2025)
The rapid advancement of digital Technology has transformed consumer purchasing behaviour, particularly in the coffee industry. This study aims to examine the impact of technology use, brand image, and perceived price on purchase decisions among customers of Tomoro Coffee. Using a quantitative method approach, this research employs purposive sampling to select respondents who have made at least one purchase through digital platforms, such as mobile apps, social media, or self-service kiosks at Tomoro Coffee outlets. Data were collected through an online questionnaire distributed to 160 respondents and analyzed using Structural Equation Modeling (SEM) to assess the relationships among variables.The findings reveal that Technology use significantly enhances purchase decisions by improving convenience and transaction efficiency. Additionally, brand image influences consumer trust and preference, reinforcing loyalty toward Tomoro Coffee. Meanwhile, perceived price has a moderate effect on purchase decisions, suggesting that while pricing remains a key factor, consumers are willing to pay a premium for quality and digital convenience. These results highlight the increasing importance of digital transformation in the coffee industry and suggest that businesses should optimize their technology-driven marketing strategies while maintaining strong brand positioning.This study contributes to marketing literature by integrating technology adoption, brand perception, and pricing strategies in the context of modern consumer behaviour. Future research could explore additional variables like service quality and customer experience to provide a more comprehensive understanding of digital consumer decision-making.